Analysis of Islamic Banking Efficiency in Indonesia in the Digital Bank Era during the Covid-19 Pandemic - Reny Fitriana Kaban; Novita Setyawati; Fayza Salsabilla Animatus Syafila; Anisa Amelia Soeminar; Mega Putri Amelia; Aqila Marza Hanifa; Pricintya Dewi (Perisai : Islamic Banking and Finance Journal, 2022)
The Islamic banking industry in Indonesia is experiencing rapid growth. Currently the world is being hit by an economic crisis triggered by the Covid-19 virus pandemic, including Indonesia, especially Islamic banking, which has also been affected by the crisis. Digital services are one of the efforts for Islamic banking to survive in the pandemic era. To survive in a situation like this, it is necessary to have input and output efficiency of the main factors in Islamic banking. Therefore, it is necessary to study the level of efficiency of Islamic banking in the era of the Covid pandemic in order to formulate corrective and anticipatory measures due to the crisis. In order to build synergies with the world of digital finance, the S1 Islamic Economics Study Program gave us an assignment on this theme. This research is quantitative in nature using data from the Financial Services Authority's annual financial statements which were analyzed using the input approach CRS method. The input variables analyzed were third party funds, labor costs, and general administrative costs, while the output variables analyzed were operating income and total financing. The results of this study indicate that the efficient banks in 2020 are Bank NTB Syariah, Bank BTPN Syariah Tbk and Bank Panin Dubai Syariah Tbk and in 2021 Bank Mega Syariah and Bank Panin Dubai Syariah Tbk. Overall, in the Covid pandemic era, the efficiency value of Islamic banking was 78.05% and was included in the moderate criteria, which was smaller than before the pandemic. More serious efforts are needed from various stakeholders to again improve the efficiency of Islamic banking by taking advantage of the benefits of digitalization.